Peninggkatan Mutu Lulusan Perguruan Tinggi Keagamaan Islam - Nur Arifin (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2021)
Improving the quality of graduates of Islamic religious colleges (PTKI) is an urgent urgency for immediate improvement. Basically, quality improvement can be done with a strategy to change one of the subsystems: people, structure, technology, and organizational processes. In relation to the study of strategies for improving quality graduates in tertiary institutions, the changes were made to the human and technology subsystems, including: (1) students being educated; (2) lecturers as educators and lecturers; and (3) facilities and infrastructure. To get students with the best seeds, a selection system that only considers quality, not the target number of students, can be done so that the output (graduates) can compete in the labor market. In addition, national standardization of the level of student ability in mastering subjects needs to be carried out through the National Examination of the Study Program. Apart from being a teacher, a lecturer is also an educator who educates prospective scholars to become human beings who have the same qualities as the purpose of education. To carry out this function, lecturers must have a functional position and improve their abilities through education to the Masters or Doctoral level as well as various seminars or training activities. Likewise with the facilities and infrastructure, which includes student practical equipment in the laboratory or adequate computerization.